HUBUNGAN FAKTOR RESIKO EKSTRINSIK DENGAN DERAJAT ASMABERULANG PADA PASIEN ASMA BRONKHIAL DI POLIKLINIK PENYAKIT DALAM - Dia Resti Dewi Nanda Demur (JURNAL KESEHATAN PERINTIS, 2017)
Asthma is a chronic inflammatory disease of the airways that is characterized recurrent attacks of breathlessness and wheezing, the situation varies in severity and frequency from person to person. Type a descriptive analytic study design with a cross-sectional study, conducted date collectionwas done july 19-2, 2015. in the study population was all patients in the clinic of bronchial asthma disease in hospitals DR.achmad Mochtar Bukittinggi. The sampling technique was accidental sampling using a questionnaire with a sample of 30 people. Analysis of the data was processed and analyzed using a computerized program with univariate and bivariate analysis using chi-square test (p<0,05). The results obtained the majority of respondents exposed to the dust factor in patients with bronchial asthma by 80%, exposure to cigarette smoke as much as 73.3%, and the factor of climate change as much as 70%. Research shows there is a significant association between the risk factors of dust, cigarette smoke risk factors and climate change risk factors (p = 0.046, p = 0.001 and p = 0.004). Based on this study concluded that the degree of asthma in patients with bronchial asthma recurring multi-factor causes. It is advisable in patients with bronchial asthma can determine risk factors for asthma relapse repeatedly to prevent a recurrence. Health services are expected to be able to provide counseling and health education to both family and for patients with bronchial asthma